Odpowiedzi

2009-10-01T12:27:34+02:00
2.6x-{1.8y-[2.2x-(y-0.6x)+1.4y]-(1.6x-0.2x)} = 2,6x - {1,8y -[2,2x + 0,6x +0,4y] - 1,4x} = 2,6x - {1,8y - 2,2x - 0,6x - 0,4y - 1,4x} = 2,6x - 1,8y + 2,2x + 0,6x + 0,4y + 1,4x =
6,8x -2,2y

(2a²b²c)⁶×(-ab²c²d)⁴= 2a¹²b¹²c⁶ * (-a⁴b⁸c⁸d⁴) = 64a¹⁶b²⁰c¹⁴d⁴
1 4 1
2009-10-01T13:22:44+02:00
2.6x-1.8y+2.2x-y+0.6x+1.4y+1.6x-0.2x = 6.8x-1.4y
(2a²b²c)⁶×(-ab²c²d)⁴=(2⁶a¹²b¹²c⁶)x(a⁴b⁸c⁸d⁴) = 64xa¹⁶xb²⁰xc¹⁴xd⁴
1 1 1
2009-10-01T15:01:28+02:00
2.6x-{1.8y-[2.2x-(y-0.6x)+1.4y]-(1.6x-0.2x)} =
= 2,6x - {1,8y -[2,2x + 0,6x +0,4y] - 1,4x} =
= 2,6x - {1,8y - 2,2x - 0,6x - 0,4y - 1,4x} =
=2,6x - {2,2y - 4,2x } =
=2,6x - 2,2y +4,2x =
=6,8x -2,2y

(2a²b²c)⁶×(-ab²c²d)⁴=
=64a¹²b¹²c⁶ * (a⁴b⁸c⁸d⁴) =
=64a¹⁶b²⁰c¹⁴d⁴